The effects of phosphorus (P) deficiency on growth and nitrogen fixation of Virgilia trees from the Cape Floristic Region (CFR) - Magadlela, Anathi (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.